Wakaf Produktif Channel YouTube Ditinjau Dari Teori Maqāṣid Syarī‘ah Ibnu ‘Ashur - Mohammad Zulfi Rhomandon; Muhammad Nabil Lubab; Murtadho Ridwan (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
This article discusses the review of Maqāṣid Syarī‘ah in the context of productive endowment on a YouTube channel based on Ibnu ‘Ashur's perspective. The study is a library research using a juridical-normative approach focused on examining the issues and solutions of productive endowments in the digital era. The research data analysis employs the IRAC method (Issue, Rules, Analysis, and Conclusion). The author opines that revenues from YouTube endowment accounts, such as income from advertisements, shopping links, revenue from YouTube premium subscriptions, channel subscriptions, Super Chat & Super Stickers, and Super Thanks, should comply with the Maqāṣid Syarī‘ah. Monetization through advertisements obtained on YouTube endowment accounts is categorized as a means (waṣīlah), where limiting advertisements by the account owner implements the principle of 'saddu zarā’i' by eliminating the causes of Sharia violations in certain content. Revenue from YouTube accounts other than advertisements is categorized as a waṣīlah in Ibnu 'Ashur's Maqāṣid, justified to attain benefits (maṣlaḥah), as these means do not contain elements violating Sharia.